Patient reading/reading patience : Oxford essays on medieval English literature - Hanna, Ralph (Liverpool : Liverpool University Press, 2017)
"This volume brings together a variety of studies, some reprinted, some new; all are devoted to the literate culture of the English later Middle Ages. The studies hover about four foci: normative English polylingualism (across three grammatically distinct languages); the messiness and discontinuities of medieval manuscript production; drawing conclusions about historical audiences/literary communities on the basis of book-evidence; and finally, the Middle English poem Piers Plowman. In general, although all the essays here arrive at broad conclusions, their point is other. The essays exemplify methods of study, the identification of problems and the recognition of tools appropriate or helpful in addressing them. Perhaps particularly the volume gestures toward a range of skills appropriate for the task; these range from narrow observation of book-production techniques to bringing a local historical record to bear on an individual volume or group of them."--
Language barriers: Literacy, schooling, universities -- Vernacular exegesis in fourteenth-century England? -- Lambeth Palace Library, MS 260, and the problem of English vernacularity -- Editing "Middle English lyrics": the case of Candet nudatum pectus -- Performing exegesis: lyric and sermon in Cambridge University Library, MS Gg.6.26. ; Nasty books: Collection procedures: Lambeth Palace Library, MS 487: some problems of early thirteenth-century textual transmission -- Producing Magdalen College MS lat. 93 -- A fifteenth-century vernacular miscellany revisited -- Humphrey Newton and Bodleian Library, MS Lat. misc. c.66. ; Historicising the archive: Yorkshire writers -- Some North Yorkshire scribes and their context -- Dr. Peter Partridge and MS Digby 98 -- John of Wales and "classicising friars." ; Still harping on - reading(:) Patience in Piers Plowman: An ideological prequel -- Langland's kind of poetry -- On Patience -- Conscience's dinner -- Hawkin and Patience's instruction -- The C version revisions.
Sisältää bibliografisia viitteitä ja hakemistoja.
Keywords: Langland, William, -- 1330?-1400?; Langland, William, -- 1330?-1400? -- Manuscripts; Langland, William, -- 1330?-1400?; Langland, William, -- 1330?-1400 -- Characters; English literature -- Middle English, 1100-1500 -- History and criticism; Manuscripts, English (Middle); Manuscripts, English (Middle) -- England -- North Yorkshire; Books and reading -- England -- History -- To 1500.